Tindak Tutur dalam Tuturan Lara Pangkon Masyarakat Ngantang - Adi Adi; Trisnian Ifianti (linguistic, literature, and teaching, 2021)
Analyzing the speech of Lara Pangkon in Ngantang this study aims to determine the forms of speech acts, explain its meaning and how the delivery of this speech. By using descriptive qualitative research methods, and narrative in Lara Pangkon as a primary source as well as the book the documentation as the source of secondary data. Acquisition of data through observation, interview, check out the note, and documentation. Data processing techniques are as follows: (1) a transcript and translation of the data, (2) the classification of the data, (3) data analysis, and (4) the exposure of the conclusion of the study. The end result of this research is there are 2(two) speech acts expressive, 2(two) said follow the directive, 2( two) speech acts assertive and 2( two) speech acts komisif are delivered with obvious can be delivered in a concise and straightforward and each speech act are said illocutionary.